Physical Education Guide, Grades K-12 - New York State Education Dept., Albany. Bureau of Curriculum Development; New York State Education Dept., Albany. Bureau of Curriculum Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This guide for a balanced physical education program identifies key activity areas, offered on a sequential basis for Grades K-12, that develop personal living skills and lead toward the objective of lifetime activity. Learning outcomes of the psychomotor, cognitive, and affective domains are addressed at each grade-level cluster. The guide provides direction through suggested program activities and, because each school community has different needs, facilities, and resources, it provides flexibility in meeting those differences. In each activities area (e.g., gymnastics, outdoor living skills, rhythm and dance), a chart is provided for checking the personal living skills developed through the activity as well as a student learning outcome evaluation outline. Specific safety considerations are addressed in the narrative of each activity area. (JD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Physical Activities; Physical Education; Physical Fitness; Program Development; Psychomotor Skills; Safety; Guides, Classroom -- Teacher